Variación de las vocales medias en el español hablado en la ciudad de La Habana: evidencia fonético-acústica - Madrid Servín, Édgar A.; Santana Cepero, Elizabeth (El Colegio de México, 2009)
This article presents the results of a study about the variation of mid vowels /e/ and /o/ in /s/-aspiration contexts in Havana City spoken Spanish. Acoustic evidence shows that the expected lengthening and opening processes in such contexts are subject of a wide phonetic variation and, for that reason, they can’t be considered as categorical processes. Vowel lengthening is an epiphenomenon, and opening has no statistical significance.